Analisa Kinerja Keuangan Bank Muamalat Syariah di Indonesia - Sri Herianingrum, Ryan. R. Maulayati, Najiatun, Muhammad Sanusi, (Jurnal Ekonomi, 2020)
The purpose of this study is to analyse the performance of a banking financial institution which is Muamalat Bank in Indonesia (BMI). Financial performance describes the condition and health of the bank. The sampling technique used in this study is saturated samples, it means all populations from 2012 to 2018 period at Muamalat Bank. The method used is multiple regression. The findings of this study are performance analysis at BMI using Non Performing Finance (NPF), Finance to Deposit Ratio (FDR), Operational Income Operating Expenses (BOPO) variables which have significant effect on Return on Assets (ROA). However NPFÂ  and BOPO variables are negatively related.